Curcumin Protects Neonatal Rat Cardiomyocytes against High Glucose-Induced Apoptosis via PI3K/Akt Signalling Pathway - Wei Yu; Wenliang Zha; Zhiqiang Ke; Qing Min; Cairong Li; Huirong Sun; Chao Liu (Journal of Diabetes Research)
The function of curcumin on NADPH oxidase-related ROS production and cardiac apoptosis, together with the modulation of protein signalling pathways, was investigated in cardiomyocytes. Primary cultures of neonatal rat cardiomyocytes were exposed to 30 mmol/L high glucose with or without curcumin. Cell viability, apoptosis, superoxide formation, the expression of NADPH oxidase subunits, and potential regulatory molecules, Akt and GSK-3β, were assessed in cardiomyocytes. Cardiomyocytes exposure to high glucose led to an increase in both cell apoptosis and intracellular ROS levels, which were strongly prevented by curcumin treatment (10 μM). In addition, treatment with curcumin remarkably suppressed the increased activity of Rac1, as well as the enhanced expression of gp91phox and p47phox induced by high glucose. Lipid peroxidation and SOD were reversed in the presence of curcumin. Furthermore, curcumin treatment markedly inhibited the reduced Bcl-2/Bax ratio elicited by high glucose exposure. Moreover, curcumin significantly increased Akt and GSK-3β phosphorylation in cardiomyocytes treated with high glucose. In addition, LY294002 blocked the effects of curcumin on cardiomyocytes exposure to high glucose. In conclusion, these results demonstrated that curcumin attenuated high glucose-induced cardiomyocyte apoptosis by inhibiting NADPH-mediated oxidative stress and this protective effect is most likely mediated by PI3K/Akt-related signalling pathway.